Challenges for central banking : perspectives from Latin America - Carrière-Swallow, Yan; International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2016)
In the wake of the 2008-09 global financial crisis, central banking and monetary policy in many corners of the world came under intense pressure and entered unchartered waters. The breadth and scale of central bank operations have been modified or expanded in unprecedented and even unimaginable ways given the circumstances. Additionally, a fundamental rethinking of central banking and its policy frameworks has been taking place. This volume reflects a multilateral effort to help close the gap in our knowledge in meeting the critical challenges presented by these significant changes, in particular, those confronting central banks in Latin America. The volume's first section provides a panoramic overview of the policy progress made to date and the challenges that lie ahead. The related issue of spillovers and monetary independence is taken up more fully in the next section. The final section presents chapters that reexamine macroprudential and monetary policies and policy frameworks from the perspective of central bank staff members from the region. (IMF)
​Foreword -- Acknowledgments -- 1 Introduction: Latin America’s Central Banking Challenges—Past, Present, and Future / Hamid Faruqee and Krishna Srinivasan -- PART I PROGRESS AND CHALLENGES: 2 A Historical Perspective on Central Banking in Latin America / Luis I. Jácome H. -- 3 Central Banking in Latin America: The Way Forward / Yan Carrière-Swallow, Luis Jácome, Nicolás Magud, and Alejandro Werner-- PART II MONETARY INDEPENDENCE IN AN INTEGRATED WORLD 4 Implications of Global Financial Integration for Monetary Policy in Latin America / Yan Carrière-Swallow and Bertrand Gruss -- 5 The Impact of the U.S. Term Premium on Emerging Markets / Alberto Naudon and Andrés Yany -- 6 Forward Guidance and Prudence in Conducting Monetary Policy / Julián Andrés Parra Polanía -- PART III MACROPRUDENTIAL POLICIES AND MONETARY FRAMEWORKS 7 Financial Stability Objectives: Drivers of Gains from Coordinating Monetary and Macroprudential Policies / Jessica Roldán-Peña, Mauricio Torres-Ferro, and Alberto Torres -- 8 A Brazilian Perspective on Macroprudential and Monetary Policy Interaction / Fabia A. de Carvalho and Marcos R. de Castro -- 9 De-dollarization of Credit in Peru: The Role of Conditional Reserve Requirements / Paul Castillo, Hugo Vega, Enrique Serrano, and Carlos Burga Index
Includes bibliographical references and index
Keywords: Banks and Banking; BANKING; CENTRAL BANKS; LATIN AMERICA